Kidnapping-Induced Trauma and secondary stress in armed conflicts: a comparative study among women in hostage families, volunteers, and the General Population - Shahar Livne; Ilana Feldblum; Sara Kivity; Naama Shamir-Stein; Einat Brand; Shir Cohen; Eran Rotman; Hagai Levine; Mor Saban (BMC, 2024)
Abstract Background Exposure to armed conflict negatively impacts health. However, there is limited data on secondary stress from ambiguous loss contexts, such as kidnapping. In this study we aimed to quantify changes in modifiable health behaviors and well-being among women in hostage families and hostage crisis volunteers versus the general female population within the first two months of the 2023 Israel-Hamas war. Methods A cross-sectional online survey was conducted on 318 Hebrew-speaking women aged 18-75 in Israel comparing: (1) a general population sample (n = 245); (2) hostage crisis volunteers (n = 40); and (3) hostage family members (n = 33). Participants provided demographic information, details on chronic illnesses, and responded to Likert-scale questions covering self-rated health, mental health, and lifestyle habits before the conflict and in current state. Results Hostage family members reported the most severe health impacts, followed by volunteers. Fair/poor physical health status increased significantly in all groups during the war, with hostages' families reporting the highest rate (61.6%). Mental health deterioration was more pronounced among hostages' families, with 84% expressing a need for mental health support. Hostages' families also reported the highest rates of sleep problems, reduced adherence to a healthy lifestyle, and weight loss. Mental and physical health declined significantly across the exposed groups, as measured by multiple assessments, with hostage families experienced the most pronounced impairments across various domains of well-being. Conclusions This period of conflict severely harmed the well-being of all women in the study population. Women from all three groups - hostage families, volunteers, and those from the general population - experienced health deterioration due to varying levels of stress and exposure to conflict-related factors. Hostage families faced the greatest impact with nearly all members of this group showing significant health damage. Long-term support is needed to help restore post-conflict health for all affected women. Further research may be needed to determine the most effective interventions for addressing these impacts across the different groups.